2013
DOI: 10.1111/ijal.12018
|View full text |Cite
|
Sign up to set email alerts
|

Social media and the institutional illusions of EU communication

Abstract: Fifteen years ago, the illusions of equality and equivalence were identified as cornerstones of EU translation. This paper revisits these concepts from a contemporary point of view. Several new official languages have been introduced, a new communication policy has been adopted, and social media tools have entered the field of EU communication. Particular emphasis is placed on virtual linguistic landscapes in the EU blogosphere and social media networks, and on the emerging language policy identifiable from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…English dominates. 93 An overhaul of the Commission's strategy in this field would thus be beneficial.…”
Section: Recommendation No 2: Implementing Political Equality By Designmentioning
confidence: 99%
“…English dominates. 93 An overhaul of the Commission's strategy in this field would thus be beneficial.…”
Section: Recommendation No 2: Implementing Political Equality By Designmentioning
confidence: 99%
“…However, research (e.g. Ammon, 2006Ammon, , 2012Author 2006;2015;Cogo & Jenkins, 2010;Gazzola, 2006Gazzola, , 2016Koskinen, 2013;Lenaerts, 2001;Piron, 1980;Quell, 1997;van Els, 2005;Wright, 2009) and internal inspections (e.g. JIU/REP/2011/4, see below) within these organisations have long shown that reductions in multilingual provision and use are commonplace, and multilingual language policies have been difficult to implement.…”
Section: Lpp and Supra-national/international Organisationsmentioning
confidence: 99%
“…Blommaert 2013). Monikielistä kielimaisemaa on tutkittu myös käännöstieteen näkökulmasta (Koskinen 2013a(Koskinen , 2013b. Tutkimuksessani sivuan vähemmistökielten tutkimusta ja sosiolingvistiikkaa, ja lisäksi tarkastelen aineistoa käännöstieteen ja verkkokielen tutkimuksen näkökulmasta hyödyntäen Reh'n (2004) monikielistämisstrategioita.…”
Section: Johdantounclassified